Manual Control Robot For Pick And Place Application - Mahasan, Mat Ali (UTeM, 2008)
Pick and place robot is a very common robot that being used in the industries for the purpose of palletizing. However the pick and place robot that being used is stationary and only capable of performing palletizing job within it’s limited working area. The manual control robot for pick and place application is designed in order to overcome this situation. The robot will be able to move around as being wish by it’s operator. As the name implies, the robot will need human handling in order to perform it’s task. This is however this is not a bad thing. By doing so, the robot will be able to perform much better because the decision is made by the most powerful computer on earth which is human brain. The construction of this robot can be divided into two different areas which is mechanical parts and also electrical and electronic parts. In the mechanical parts, the rigidity of the whole robot structure, the effectiveness of the gripper and also the lifting mechanism. The design and development of the mechanical structure had being done using Solid Works software which had enable the design to be prototype first before actual fabrication can be carried out. This method had save lots of time in the fabrication process because all the parts for the robot had been predetermined. The electrical and electronic areas consist of the driver circuit, PIC circuit, hand hold controller, programming and also the whole robot wiring. The most important part in this section is how to suppress the electrical noise. Electrical noise can be a big problem in electrical and electronic because it can cause the whole system to malfunctions. This particular robot however had managed to overcome that by using a few methods that had being researched and practice such as by using an opto-isolator in the driver circuit. Besides that the whole robot wiring is also being done with noise suppression in mind. By combining the mechanical and also the electrical and electronic parts together, the robot had managed to function remarkable well were able to do it’s task with flying colours.